2017
DOI: 10.1108/jhom-04-2016-0073
|View full text |Cite
|
Sign up to set email alerts
|

Size does matter – span of control in hospitals

Abstract: Purpose Centralization, mergers and cost reductions have generally led to increasing levels of span of control (SOC), and thus potentially to lower leadership capacity. The purpose of this paper is to explore how a large SOC impacts hospital staff and their leaders. Design/methodology/approach The study is based on a qualitative explorative case study of three large inpatient wards. Findings The study finds that the nursing staff and their frontline leaders experience challenges in regard to visibility and rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 42 publications
0
43
0
3
Order By: Relevance
“…For instance, some viewed span of control as only the charge nurses who report directly to them whereas others considered span of control as referring to all full‐time equivalent bedside nurses on all shifts in their units. Indeed, scholars have described this concept in similar terms but the literature lacks a definitional consensus (Cupit et al, ; Holm‐Petersen et al, ). Future studies should consider span of control's impact on nurse managers' communication strategies and mentoring patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, some viewed span of control as only the charge nurses who report directly to them whereas others considered span of control as referring to all full‐time equivalent bedside nurses on all shifts in their units. Indeed, scholars have described this concept in similar terms but the literature lacks a definitional consensus (Cupit et al, ; Holm‐Petersen et al, ). Future studies should consider span of control's impact on nurse managers' communication strategies and mentoring patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Staffing is a common concern among international nurse managers because staffing not only affects the placement of nurses and the organisation of nursing teams (Cupit, Stout‐Aguilar, Cannon, & Norton, ; Holm‐Petersen, Østergaard, & Andersen, ; Jooste & Prinsloo, ; Maenhout & Vanhoucke, ; North et al, ), but it also influences how nurses relate to and support one another (Feather, Ebright, & Bakas, ; Gazaway, Anderson, Schumacher, & Alichnie, ; Gittell, ; Holland, Cooper, & Sheehan, ; McCabe & Sambrook, ). Despite the burgeoning interest in how managers communicate and support their nurses (Brunetto, Farr‐Wharton, & Shacklock, ; Hartung & Miller, ; Marx, ; Rouse & Al‐Maqbali, ; Timmins, ), the literature offers limited insights into how the proliferation of nurses' varied work arrangements affects the mentoring and support that nurses receive from their managers (Gan, ; Jones, ).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we study a horizontal merger in which two full-scale hospitals were merged with a third large university hospital into one unit. This new organization was much larger than the pre-merger organizations (Holm-Petersen et al, 2017).…”
mentioning
confidence: 95%
“…A further, less examined limitation of these methods is that they do not account for any workload associated with variability in casemix. A small number of studies have found cohorting of patients with similar conditions improves quality of care and decreases cost (Duffield et al, ), while two qualitative studies observed that nurses perceive their work to be more complex with more varied casemix due to the increasingly specialist knowledge and skills needed to appropriately care for patients (Diers et al, ; Holm‐Petersen, Østergaard, & Andersen, ).…”
Section: Introductionmentioning
confidence: 99%